Exploring the use of community of inquiry strategy in English second language learners writing skill - Khadidja, Akakba (Kulliyyah of Education, International Islamic University Malaysia, 2016)
The current study aimed to explore the effects of 'Community of Inquiry' (COI) pedagogy on ESL learners' writing skill following Fascione's six core critical thinking skills of: interpretation, analysis, evaluation, inference, explanation and self-regulation. The study also sought to explore the kind of language used by ESL learners in their writing when engaging in critical thinking after experiencing COI. The study applied a qualitative research methodology, namely 'case study'. The data was analysed using documentary analysis of fifth grade students' writing. The overall findings showed that ESL learners' writing included five out of the six core critical thinking skills, excluding self-regulation. Learners were seen to apply multiple sorts of language relating to these critical thinking skills. The main genre or style of writing was argumentative as a result of exposure to COI philosophical discussions.